Primer of educational research - Suter, W. Newton (Boston : Allyn and Bacon, 1998)
This advanced undergraduate or graduate level introduction to research methods presents the skills needed to critically evaluate published educational research for students of education and the social sciences. Chapters include constructs, variables, and hypotheses; research as a process; the hypot
Includes bibliographical references
Keywords: Education -- Research -- Methodology